Perbandingan Efektivitas Penggunaan Obat Oral Antiabetik Tunggal dan Kombinasi pada Pasien Diabetes Mellitus Tipe 2 di Rumah Sakit Umum Royal Prima Medan - Ega Yos Sanda; Muhammad Yunus; Erida Novriani (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels, with a high prevalence in Indonesia. Pharmacological therapy using oral antidiabetic medications (OAD), either singly or in combination, is a primary approach to managing type 2 DM. Evaluating the effectiveness of therapy is essential to ensure the achievement of glycemic targets and to prevent complications. This study aims to compare the effectiveness of using single and combination oral antidiabetic medications in reducing blood glucose levels in patients with type 2 Diabetes Mellitus at Royal Prima General Hospital Medan. This study is a non-experimental observational study, utilizing a retrospective descriptive design with a cross-sectional approach. A sample of 60 patients with type 2 DM who were hospitalized between January - June 2024, consisted of 30 patients on single therapy and 30 patients on combination therapy. Data was taken from medical records, and the effectiveness was assessed based on the decrease in blood sugar levels over six days of treatment. The results of this study show that the average percentage decrease in blood sugar levels over 6 days for single oral antidiabetics was 28.87%, and the average reduction in blood sugar levels for combination antidiabetics was 31.34%. Combination therapy shows higher effectiveness in reducing blood sugar levels compared to single therapy. There is a difference in effectiveness between single OAD therapy and combination therapy in patients with T2DM. Combination therapy tends to be more effective and can be a rational alternative for patients who do not reach glycemic targets with monotherapy.